A study of the impact of product packaging on the buying behavior of the consumer-buyer - Agbisit, Romeo S. (1988)
50 individual residing in three different residential areas in Baguio City namely: Government Center Subdivision, Upper Q.M., and Fil-Am Compound were taken as respondents in this research. Stratified random method was used in the selection of respondents. The main objective of this study, is to determine the effect of packaging on consumer's behavior. The research involved testing on the different attributes of the consumer namely: sex, educational attainment, income level,and age level which are hypothesized to have an effect on the buying behavior of the consumer. Data collection was administered thru the uses of a 3-page structured interview schedule. The interview schedule consist of the personal information of the respondents, current consumer behavior, evaluation on current package design, and the respondent's personal opinion on product packaging. The working framework of the study includes only three products namely: bath soaps, soft-drinks and toothpaste. Exhibits/drawings of the three products were also presented in this study so as to eliminate other intervening variables such as to brand loyalty, price, etc...Frequencies and percentages were used to analyze the respondent's answer and in the analysis of the relationship of the different variables so as to come up with clear cut answers regarding the different objectives of the study. Based on the results obtained it was found out that the respondent's preference of brands and packaging design differ on terms of sex, educational attainment, income level, and age level. As a whole, the findings obtained from this study shows that package design has an effect on consumer's product preference and likewise, sex, educational attainment, income level and age level -- Author's abstract.